1968
DOI: 10.1902/jop.1968.39.6.311
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Radiographs and Pocket Measurements in Periodontal Disease Evaluation

Abstract: UNTREATEDPERIODONTAL DISEASE leads in time to decreased height of the supporting alveolar bone. Longitudinal studies of periodontal disease require that accurate determinations be made at specified intervals of the amount of bone loss around teeth. In clinical practice, general practitioners and periodontists depend on both radiographs and pocket measurements for information about the extent of bone loss in their patients.There is disagreement about the relative accuracy with which radiographs and pocket measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 5 publications
3
37
1
2
Order By: Relevance
“…Suomi et al 51) (1968) also found no difference in bone loss between proximal sites. The fact that distal sites had higher bone loss may also be explained by the fact that the distal surface of the lower canines, for example, is characterized by deeper and wider concavities 48) .…”
Section: Resultsmentioning
confidence: 93%
“…Suomi et al 51) (1968) also found no difference in bone loss between proximal sites. The fact that distal sites had higher bone loss may also be explained by the fact that the distal surface of the lower canines, for example, is characterized by deeper and wider concavities 48) .…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, evaluation of radiographs tends to underestimate the extent of alveolar bone loss compared with the gold standard of intrasurgical measurements. 1,3,[5][6][7][8] In some cases where 3D imaging is required (e.g. complex implant cases), cone beam volume tomography may overcome the limitations of intraoral radiographs; however, this results in higher exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, radiographic assessment tends to underestimate the amount of bone loss. 1,[4][5][6][7][8][9][10] Digital processing and manipulation of radiographic images may improve diagnostic interpretation of radiographs in terms of reliability and accuracy. Using a computerassisted analysing system, the accuracy of linear measurements of periodontal bone loss could be improved compared with conventional methods, such as using a loupe.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, it is assessed by using a probing procedure, but the anatomical complexity in this region often reduces its accuracy. 3,4 Although radiographic diagnosis is likely to underestimate the furcation bone loss in comparison with the probing procedure, 4,5 intraoral radiography plays an adjunctive role in the diagnosis. 4,6 It is recommended that intraoral radiographs should be taken at different X-ray beam angles to reduce the risk of missing furcation involvement.…”
Section: Introductionmentioning
confidence: 99%